UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN KELOR (MORINGA OLEIFERA) TERHADAP BAKTERI PEMBUSUK IKAN SEGAR (PSEUDOONAS AERUGINOSA) - Widowati, Imas; Efiyati, Siti; Wahyuningtyas, Sari (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
The objective of the research is to find out whether the extract of kelor(Moringa oleifera) leaves can be used as antibacteria of decomposer bacteria (Pseudomonasaeruginosa) in fresh fish and to find out the most effective concentration ofkelor extract as antibacteria. The research starts with making the extract of kelor(Moringa oleifera) leaves by using maceration technique. The next step is makingNatrium Agar (NA) as the medium for growing the bacteria and the third step istesting the extract of kelor (Moringa oleifera) leaves on the bacteria (Pseudomonasaeruginosa) by using the aseptic technique and streak plate method. The bacteriawere incubated for approximately 24 hours in the room temperature. Next, thediameter of the clearzone produced in each treatment is measured. In this researchthere are five variations of kelor leaf extract concentrations, namely 0%, 25 %, 50%,75%, and 100% with five repetitions. Based on the SPSS analysis using Anava testing,the significance level is 0.007 ≥ 0.005. It shows those five treatments of giving theextract of kelor leaves with the concentrations of 0%, 25%, 50%, 75%, and 100% donot significantly affectthe activities of Pseudomonas aeruginosa bacteria. Based on theresult of the observation, the average length of the diameter of clear zone on theextract concentration of 50% is the biggest, which is 1 mm long. Thus, it can be concludedthat the extract of kelor (Moringa oleifera) leaves can be used as antibacteriafor the decomposer (Pseudomonas aeruginosa) bacteria of fresh fish.